2011
DOI: 10.1097/sla.0b013e3182117b24
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Outcomes and Complications After Laparoscopy-assisted Pylorus-preserving Gastrectomy for Early Gastric Cancer

Abstract: Laparoscopy-assisted pylorus-preserving gastrectomy is a safe operation with excellent postoperative outcomes in terms of minimized major complications based on the Clavien-Dindo classification in patients with EGC in the middle third of the stomach. To prevent postoperative complications, surgeons need to ensure an extra leaning period for LAPPG, and LAPPG should be performed cautiously in patients with high BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 24 publications
9
73
1
Order By: Relevance
“…The observed relatively high incidence of gastric stasis may be due to the lack of experience for the particular technique. This was also indicated in our previous study on LAPPG where surgical experience was a significant factor for lower incidence of postoperative complications [9]. Thus, the results may improve by standardization of the procedure.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The observed relatively high incidence of gastric stasis may be due to the lack of experience for the particular technique. This was also indicated in our previous study on LAPPG where surgical experience was a significant factor for lower incidence of postoperative complications [9]. Thus, the results may improve by standardization of the procedure.…”
Section: Discussionsupporting
confidence: 50%
“…The operation time for TLPPG was approximately 30 min longer than the previously reported operation time for LAPPG [9]. It is most likely that the longer operation times recorded for TLPPG in this study were due to the necessity of performing an intraoperative gastroscopy in all cases to determine the resection line for the stomach, whereas the location of the tumor is verified easily in the LAPPG procedure by palpating preoperatively placed marking clips.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…A feature of the Clavien-Dindo classification is that different risk factors could be identified for complications of different severity in the same population. We did not include surgical experience as a variable in the analyses although it is reported to be one of the independent risk factors of postoperative complication in LAG [35]. The reason for this non-inclusion is that operator selection is a potential risk of bias because difficult cases tended to be operated by experts and some of the relatively easy cases are done by trainees, particularly in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al [56] reported the short-term outcomes of 307 LAPPGs. The mean operation time was 229.4 min, the estimated blood loss was 49.1 mL, and the mean total number of dissected lymph nodes was 31.6.…”
Section: Laparoscopic Function-preserving Surgerymentioning
confidence: 99%